INTERVENTION OF PROVIDING BLACK GLUTINOUS RICE PORRIDGE TO INCREASE MOTHER'S MILK PRODUCTION - Indrayani, Triana; Herlina, Novia; Romlah, Siti (Yayasan Education and Social Center, 2024)
Breastmilk is an essential intake for babies, particularly for their initial stage of life. Breastmilk is liquid produced by breast glands. The low achievement of exclusive breastmilk can affect the quality of future human resources, thus affecting the national economy. In addition, breastmilk that cannot be released smoothly can cause the occurrence of mastitis in mothers, and the babies who do not receive the breastmilk will be susceptible to suffering from diseases. This community service was conducted to educate pregnant mothers in increasing their breast milk production. This community service was conducted at TPMB N Depok, West Java, in January 2024. The research instrument used was in the form of an observation sheet. Furthermore, this community service was carried out by first preparing the SOP and black glutinous rice porridge, which was further used as the intervention. This activity involved 30 respondents to educate the mothers about the benefits of black glutinous rice porridge in increasing breastmilk production and demonstrating how to make the black glutinous rice porridge. In this case, the black glutinous rice porridge was consumed for a week. As a follow-up, an evaluation was conducted using an observation sheet to measure the smooth production of breast milk. Furthermore, results revealed that black glutinous rice porridge effectively smoothened breastmilk production. In this case, among 30 respondents participating in the community service activity and intervention of consuming the black glutinous rice porridge for a week, only one person, or 3.3% of the respondents, experienced unqualified breastmilk